Long-term effects of an intensive interventional training program based on activities for individuals with spinal cord injury: a pilot study. (17th November 2015) - Padula, Natalia; Costa, Mariana; Batista, Alexsandro; Gaspar, Roberta; Motta, Camilo; Palma, Gisele; Torriani-Pasin, Camila
Abstract: Objectives : To investigate the long-term effects of a rehabilitation program using activity-based therapies in daily activities and the participation of individuals with spinal cord injury (SCI). Method : A descriptive study of case reports assessing the performance of daily activities and quality of life as a dependent variable, using the Functional Independence Measure (FIM) and the Short-Form Health Survey (SF-36), respectively. Seven individuals were included in the intervention composed of a multimodal intensive therapies program based on activities (activity-based therapy, ABT) conducted for 18 months. Results : It was possible to descriptively observe that the individual with the shortest time of injury and previous training obtained the largest variation in the FIM score. But no statistically significant difference was found in the assessments. Conclusion : For trained individuals with chronic SCIs, classified "A" according to the American Spinal Injury Association (ASIA), an ABT program did not significantly affect the scores of the scales used to assess quality of life (SF-36) and functional independence (FIM).